2020
DOI: 10.1038/s41598-020-74965-2
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of miR-223 in sepsis-induced mortality

Abstract: Lymphocyte apoptosis appears to play an important role in immunodysfunction in sepsis. We investigated the role of miR-223 in cell proliferation and apoptosis to identify potential target downstream proteins in sepsis. We recruited 143 patients with sepsis and 44 healthy controls from the Chinese PLA General Hospital. Flow cytometry was used to sort monocytes, lymphocytes, and neutrophils from fresh peripheral blood. A miR-223 mimic and inhibitor were used for transient transfection of Jurkat T cells. Quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…miR‐223 has been shown to promote the apoptosis of various cell types, such as HepG2 cells, mast cells and cardiomyocytes 26–28 . On the other hand, miR‐223 also could inhibit apoptosis and promote the proliferation of lymphocytes and keratinocytes 29,30 . The dual role of miR‐223 in cell apoptosis may be a result of miR‐223 target different genes in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐223 has been shown to promote the apoptosis of various cell types, such as HepG2 cells, mast cells and cardiomyocytes 26–28 . On the other hand, miR‐223 also could inhibit apoptosis and promote the proliferation of lymphocytes and keratinocytes 29,30 . The dual role of miR‐223 in cell apoptosis may be a result of miR‐223 target different genes in different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that miR-223 was downregulated after severe CLP surgery, with an increase of inflammatory response and myocardial depression. Some clinical studies supported these findings, showing a reduction of serum miR-223 in patients who died of sepsis [ 33 , 34 ]. It is noteworthy that a decrease in seric level of miR-223 was also linked with cardiac mortality in chronic kidney disease patients [ 35 ].…”
Section: Resultsmentioning
confidence: 84%
“…One of characteristics for early sepsis is the excessive inflammation syndrome called “cytokine storm” ( 26 ). IL-6 is one of the most commonly used biomarkers of sepsis, and the level of IL-6 is positively correlated with sepsis-associated organ dysfunction and death ( 8 , 27 ).…”
Section: Discussionmentioning
confidence: 99%